Evaluation of genome and base editing tools in maize protoplasts - Fierlej, Yannick; Jacquier, Nathanaël M. A.; Guille, Loïc; Just, Jérémy; Montes, Emilie; Richard, Christelle; Loue-Manifel, Jeanne; Depège-Fargeix, Nathalie; Gaillard, Antoine; Widiez, Thomas; Rogowsky, Peter M. (Frontiers in Plant Science, 2022)
Despite its rapid worldwide adoption as an efficient mutagenesis tool, plant genome editing remains a labor-intensive process requiring often several months of in vitro culture to obtain mutant plantlets. To test, in only a few days, the efficiency of molecular constructs or novel Cas9 variants (clustered regularly interspaced short palindromic repeats (CRISPR)-associated protein 9), a streamlined maize protoplast system coupled to NGS (next generation sequencing) analysis and a novel bioinformatics pipeline was established. Mutation types found with high frequency in protoplasts had a trend to be the ones observed after stable maize transformation. The protoplast system also allowed to conclude that modifications of the sgRNA (single guide RNA) scaffold leave little room for improvement, that relaxed PAM (protospacer adjacent motif) sites increase the choice of target sites for genome editing, albeit with decreased frequency, and that efficient base editing in maize could be achieved for certain but not all target sites. Phenotypic analysis of base edited mutant maize plants demonstrated that the introduction of a stop codon but not the mutation of a serine predicted to be phosphorylated in the bHLH (basic helix loop helix) transcription factor ZmICEa (INDUCER OF CBF EXPRESSIONa) caused abnormal stomata, pale leaves and eventual plant death two months after sowing.